2021
DOI: 10.1155/2021/2319412
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Mediates Mitochondrial Autophagy via miR-30b and the NIX/BNIP3 Signaling Pathway in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is regarded as a severe neurodegenerative disorder. Baicalein is involved in the treatment of PD. This study explored the mechanism of baicalein in PD. The PD rat model was established using 6-hydroxydopamine. The neurologic score, dopamine (DA) content, apoptotic cells, and neuronal damage were evaluated after rats were treated with baicalein. Autophagy in PD rats was inhibited using 3-methyladenine (3-MA). The mitochondrial membrane potential (MMP) and autophagy-related proteins (LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, Zhang et al suggested that pretreatment of PC12 cells with baicalein inhibited H 2 O 2 ‐induced apoptosis by mitigating mitochondrial dysfunction (by inhibiting membrane potential loss, reducing cytochrome c release, upregulating Bcl‐2 expression, and downregulating Bax level in the mitochondria) and suppressing oxidative stress (by inhibiting mitochondrial ROS generation and lipid peroxidation) (Zhang, Ye, & Dong, 2010). Other studies have indicated that baicalein exerted protective effects against 6‐OHDA‐induced neurotoxicity both in vitro and in vivo through various mechanisms, which involved the activation of the Keap1/Nrf2/HO‐1 pathway, mediation of the PKCα and PI3K/AKT pathways, and promotion of mitophagy (via miR‐30b‐5p and the SIRT1/AMPK/mTOR pathway, as well as miR‐30b and the NIX/BNIP3 pathway) (Chen et al, 2021a; Chen et al, 2021b; Zhang et al, 2012). Furthermore, Zhang et al demonstrated that baicalein protected against rotenone‐induced injury in rat and SH‐SY5Y cell models by enhancing mitobiogenesis through increasing the levels of peroxisome proliferator‐activated receptor gamma coactivator‐1α (PGC‐1α), nuclear respiratory factor‐1 (NRF‐1), and mitochondrial transcriptional factor A (TFAM) via the cAMP‐responsive element‐binding protein (CREB) and glycogen synthase kinase‐3β (GSK‐3β) pathways (Zhang et al, 2017).…”
Section: Therapeutic Effects Of Natural Compounds On Pd By Modulating...mentioning
confidence: 99%
“…Similarly, Zhang et al suggested that pretreatment of PC12 cells with baicalein inhibited H 2 O 2 ‐induced apoptosis by mitigating mitochondrial dysfunction (by inhibiting membrane potential loss, reducing cytochrome c release, upregulating Bcl‐2 expression, and downregulating Bax level in the mitochondria) and suppressing oxidative stress (by inhibiting mitochondrial ROS generation and lipid peroxidation) (Zhang, Ye, & Dong, 2010). Other studies have indicated that baicalein exerted protective effects against 6‐OHDA‐induced neurotoxicity both in vitro and in vivo through various mechanisms, which involved the activation of the Keap1/Nrf2/HO‐1 pathway, mediation of the PKCα and PI3K/AKT pathways, and promotion of mitophagy (via miR‐30b‐5p and the SIRT1/AMPK/mTOR pathway, as well as miR‐30b and the NIX/BNIP3 pathway) (Chen et al, 2021a; Chen et al, 2021b; Zhang et al, 2012). Furthermore, Zhang et al demonstrated that baicalein protected against rotenone‐induced injury in rat and SH‐SY5Y cell models by enhancing mitobiogenesis through increasing the levels of peroxisome proliferator‐activated receptor gamma coactivator‐1α (PGC‐1α), nuclear respiratory factor‐1 (NRF‐1), and mitochondrial transcriptional factor A (TFAM) via the cAMP‐responsive element‐binding protein (CREB) and glycogen synthase kinase‐3β (GSK‐3β) pathways (Zhang et al, 2017).…”
Section: Therapeutic Effects Of Natural Compounds On Pd By Modulating...mentioning
confidence: 99%
“…Its anti-neuroinflammatory properties have been associated with the inhibition of the expression of inducible nitric oxide synthase, the production of NO and the nuclear factor-ḳB-signalling pathways in glial cells [ 150 ]. The involvement of baicalein in the treatment of PD has been also linked to its ability to restore DA content, neurons, mitochondrial membrane potential, and mitochondrial autophagy protein levels [ 153 ].…”
Section: Innovative Formulations Designed To Enhance the Central Effe...mentioning
confidence: 99%
“…B-signalling pathways in glial cells [150]. The involvement of baicalein in the treatment of PD has been also linked to its ability to restore DA content, neurons, mitochondrial membrane potential, and mitochondrial autophagy protein levels [153].…”
Section: Baicalein Involved In the Design Of New Formulations Against...mentioning
confidence: 99%
“…It contains the LIR motif which enables it to regulate mitophagy via parkin-independent pathway. BNIP3 protein levels were found to be decreased in PD [ 29 ]. Recently Zhang et al have shown that increased BNIP3 binds to PINK1 and decreases the proteolytic cleavage of PINK1 resulting in activation of parkin-dependent mitophagy [ 30 ].…”
Section: Introductionmentioning
confidence: 99%